Islamic Music Art of Gamelan Kiai Kanjeng in the Plurality of Indonesia - Mahadika, Alam; Misbahuddin, Angga (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2023)
The Kiai Kanjeng Musical Arts Group has a strategic position and distinct function. It does not only play musical performances but also participate in helping people’s life problems through communication and dialogue in the context of Islamic pluralism. This research was to examine the Kiai Kanjeng Music Group, pluralistic dialogue, and conflict resolution. This study used a descriptive-qualitative approach with a two-stage data collection method. First, a comprehensive literature review to identify relevant sources such as books, journal articles, and research reports related to gamelan music, Islam, and pluralism in Indonesia. Second, an online search to access traditional music archives, gamelan performance recordings, and audiovisual resources related to the Kiai Kanjeng Gamelan Music Group. The findings of this study were: the Kiai Kanjeng Music Group played traditional and modern types of music. During the performance, the group had a dialogue and discussion session with the audiences. Finally, the Kiai Kanjeng Music Group was able to touch on aspects of social life by offering solutions and mediating major conflicts through a special methods.